Combatting Tax Evasion: Evidence from Comparing Commercial and Business Tax Registry - Collen Lediga; Nadine Riedel; Kristina Strohmaier (Center for Economic Studies and ifo Institute (CESifo), 2018)
In 2008 and 2014, the South African Revenue Service (SARS) did snapshot synchronizations of its business tax registry with the country's commercial register in an attempt to identify firms that are non-compliant with their obligation to register with SARS for business tax purposes. We analyse these interventions drawing on SARS's business tax registry and the population of business tax returns between 2009 and 2014. Several findings emerge. First, in both years, the comparisons resulted in the identification of around 300,000 non-compliant taxpayers, providing prima facie evidence of significant extensive-margin tax evasion. The interventions significantly raised South African business tax revenues in the following years despite the fact that the identi-fied `extensive-margin evaders' exhibit a lower propensity to submit tax returns and, conditional on return submission, report less income than comparable entities that voluntarily registered with SARS. The analysis further suggests that the observed gap in reported taxable income relates to underlying differences in firm size and corporate profitability rather than intensive-margin tax evasion. In line with `missing middle theories', extensive-margin evaders that submit tax returns are, moreover, found to exhibit increased sales and asset growth after their forced registration with SARS.
Keywords: H20; H70; 330; tax evasion; less developed countries; tax administration